2016
DOI: 10.3389/fmicb.2016.01642
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Functional Diversity of Soil and Hypolithic Microbial Communities in Miers Valley, McMurdo Dry Valleys, Antarctica

Abstract: The McMurdo Dry Valleys of Antarctica are an extreme polar desert. Mineral soils support subsurface microbial communities and translucent rocks support development of hypolithic communities on ventral surfaces in soil contact. Despite significant research attention, relatively little is known about taxonomic and functional diversity or their inter-relationships. Here we report a combined diversity and functional interrogation for soil and hypoliths of the Miers Valley in the McMurdo Dry Valleys of Antarctica. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 58 publications
9
52
3
Order By: Relevance
“…The comprehensive analyses of the microbiome of rocks and soils revealed that the Proteobacteria and Actinobacteria were two of the most abundant bacterial phyla, as occurs with other (non-)polar and alpine retreating glacier forefields (Babalola et al, 2009;Zumsteg et al, 2012;Bajerski and Wagner, 2013;Makhalanyane et al, 2013;Brown and Jumpponen, 2014;Pessi et al, 2015;Jiang et al, 2018). These classes are known to include a number of phototrophic, photoheterotrophic and chemolithotropic taxa able to thrive in the oligotrophic niches represented by recently exposed rocks and soils (Kersters et al, 2006;Rime et al, 2016;Wei et al, 2016). Our data showed an uneven and generally low abundance of Cyanobacteria, a scenario in agreement with results of Ji et al (2016), who revealed low abundances of Cyanobacteria coupled with a predominance of Chloroflexi, Actinobacteria and Proteobacteria in ice-free soils in the Mitchell Peninsula (East Antarctica).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The comprehensive analyses of the microbiome of rocks and soils revealed that the Proteobacteria and Actinobacteria were two of the most abundant bacterial phyla, as occurs with other (non-)polar and alpine retreating glacier forefields (Babalola et al, 2009;Zumsteg et al, 2012;Bajerski and Wagner, 2013;Makhalanyane et al, 2013;Brown and Jumpponen, 2014;Pessi et al, 2015;Jiang et al, 2018). These classes are known to include a number of phototrophic, photoheterotrophic and chemolithotropic taxa able to thrive in the oligotrophic niches represented by recently exposed rocks and soils (Kersters et al, 2006;Rime et al, 2016;Wei et al, 2016). Our data showed an uneven and generally low abundance of Cyanobacteria, a scenario in agreement with results of Ji et al (2016), who revealed low abundances of Cyanobacteria coupled with a predominance of Chloroflexi, Actinobacteria and Proteobacteria in ice-free soils in the Mitchell Peninsula (East Antarctica).…”
Section: Discussionmentioning
confidence: 98%
“…This is especially true for the lithic niche, as suggested by our results of electron microscopy showing colonization of these autotrophic bacteria only after ∼13 years since glacial retreat. Alternatively, it is also likely that in our study area these bacteria colonize other non-sampled microhabitats such as the hypolithic (e.g., Cowan et al, 2010;Wei et al, 2016), or are associated with moss-dominated cryptogamic covers (e.g., Arróniz-Crespo et al, 2014). It is however remarkable that the Burkholderiales (a group of diazotroph Betaproteobacteria) were more abundant at the first successional states of both substrates, suggesting that these bacteria could play an important role for initial colonization through nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry Valleys soils are highly oligotrophic and support relatively low biomass (Smith et al, 2006;Pointing et al, 2009;Rao et al, 2011;Lee et al, 2012). In this area, soil communities are dominated by Actinobacteria and other cosmopolitan taxa (Aislabie et al, 2006;Smith et al, 2006;Niederberger et al, 2008Niederberger et al, , 2012Stomeo et al, 2012), while cyanobacteria-dominated biofilms are predominant in hypolithic communities (Chan et al, 2012;de los Ríos et al, 2014a;Wei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have improved knowledge of the microbial diversity and composition of these ecosystems (Wei et al, 2016; Archer et al, 2017) and provided important insights to clarify the complex relationship between environmental parameters (i.e. altitude and distance from sea) and biodiversity (Selbmann et al, 2017; Coleine et al, 2018a, b).…”
Section: Discussionmentioning
confidence: 99%